Badiou in China?: Re-translations of French Maoism and inaesthetics. (1st September 2014) - Wright, Colin
This article explores the origins of Alain Badiou's philosophy of art in his engagements with Maoism in order to speculate about the potential impact of that philosophy on contemporary Chinese art and art criticism. Utilizing the broad concept of 'translation', the article first situates Badiou's position on art in relation to the translation of Maoism in France and his personal participation in France's experience of May 1968. It is then argued that French Maoism was interpreted through pre-existing avant-gardist models of aestheticized politics that largely departed from what was happening in China during the Cultural Revolution. By understanding Badiou's critique of the depoliticizing effects of this avant-gardist conflation of art and politics, it is possible to understand more clearly his later concept of 'inaesthetics'. Although it is a theoretical piece, this article aims to encourage a mutual 'translation' between Badiou's work and contemporary Chinese art and art criticism.